Household energy consumption tendencies: The Baltic States context - Grigolienė, Rasa; Kiyak, Deimena; Šimanskienė, Ligita; Labanauskaitė, Daiva; Župerkienė, Erika; Mishenina, Halyna (Journal of Business Economics and Management, 2024)
As energy resource prices are on the rise and the stability of energy supplies is increasingly challenged by the current geopolitical climate, it is essential to scrutinize the capability of households to adapt to the resulting circumstances by assessing the current and potential household energy supply and adapting solutions to energy consumption habits. The aim of the research is to study of the energy consumption behaviour of households in the Baltic States amidst a significant increase in prices. The research methods encompass the examination of literary sources, categorization, amalgamation, abstraction, and juxtaposition in the theoretical segment, as well as a case study focusing on energy consumers in Lithuania, Latvia, and Estonia. Notably, the study presents a unique analysis of the unprecedented scenario of substantial price hikes across all energy usage categories in the region. An examination of individual responses concerning energy consumption illustrates a notable escalation in household expenditures on electricity and heating. Households are endeavouring to curtail energy expenses through various conservation techniques. A correlation between income levels and household energy consumption is evident.